Influence of Excessive Expenditure of the Government in Perspective of Interest Rate and Money Circulation Which in Turn Affects the Growing Process in Pakistan - Rahman, Zia-Ur- (Asian Journal of Economics and Empirical Research, 2019)
In this study an attempt was made to investigate the affiliation among the excessive expenditure, interest rate, inflation, money supply and growing rate. For this purpose, time series data comprises 1976 to 2018 were collected from the Handbook and world development indicator. The analyses show a good number of findings. Firstly, the unit root test results show that all the variables are stationary at level, except inflation but appear stationary at first difference. However, ZA test pronounces structural break in the data with a different time period. This of course leads the study to determine the short and long-term association among the variables. The vector error correction and Johansen cointegration reveals the short and long-run relationship exists among the variables. While excessive expenditure and the money circulation have one-way granger causality with the growth rate. Moreover, the diagnostic and stability tests describe that model specification, auto correlation and model are normal. Even impulse response pronounces that all the variables would have a positive influence on the growth rate in the future. Based on this, the study recommends that government should not create the atmosphere of the crowding out. No doubt interest rate favors the economy, but government should also manage its expenditure.